Design of LC Filter for Locomotive Auxiliary Converter - CHEN Xiang; XIONG Yuyu; WANG Jiajia; LUO Dewei; YANG Xingxian (Kongzhi Yu Xinxi Jishu)
In this paper, the main circuit structure of LC filter for locomotive auxiliary converter was described, analytical expression of output voltage for bipolar SPWM modulation strategy was given and Harmonic characteristics, inductor current and output voltage of the inverter were analyzed. In order to reduce the weight and volume of locomotive auxiliary converter LC filter on the premise of meeting the requirements of the output voltage harmonic content, it proposed a design method of voltage-type auxiliary converter LC filter from the aspect of LC characteristic impedance, and the proposed LC filter has been verified through field application.